Differences in Pain between Topical Gel and Chlor Ethyl in Paedodontic Patients before Infiltration Anesthesia - Sri P. Pandu; Sherly Horax; Marhamah Marhamah; Amelia Amelia (e-GiGi, 2024)
Abstract: Pain control during invasive and non-invasive dental procedures is very important since discomfort can cause patients to refuse treatment. Local anesthesia (LA) is required in any dental practice, including pedodontics, to reduce pain during dental procedures such as extractions, pulpotomy, root canal treatment, pulpectomy, abscess drainage, and minor oral surgical procedures. Application of flavoured topical anesthetic gel is most frequently used in pediatric dentistry. There are various types of topical anesthetics according to the medicinal ingredients in the forms of liquid, gel, and spray. This study aimed to find out the difference between the use of topical gel and chlorine ethyl in paedodontic patients before infiltration anesthesia at Paedodontics Department of rsgm Baiturrahmah. This was a descriptive and observational study with a cross sectional design. The topical anesthetics used were topical gel and chlorine ethyl; each for 10 patients. Data were obtained directly from student observations of the patient's face during topical anesthesia using the Visual analog Scale (VAS). The results showed that most patients were 9 years old (35.0%); female (65.0%). Most of the VAS results were found in the "like" criterion namely as many as eight respondents (40.0%); six of them were female (75%). Topical gel was the most topical anaesthetic type used with "like" criterion of VAS, as many as eight respondents (100%). In conclusion, most of the VAS results in the "like" criterion for topical gel indicating that topical gel is an effective anesthetic to reduce pain in pediatric patients. Keywords: pain; anxiety; topical gel; chlor ethyl; visual analogue scale